Entrance Surface Dose (ESD) Measurement During Pediatric Chest X-Rays - Roya Davoodi; Mohammad Reza Eydian; Reza Rezazadeh-Farokh; Asma Maraei (Journal of Radiation and Nuclear Medicine, 2020)
Introduction Given the high radiation tissue sensitivity of pediatric patients, it is necessary to monitor their received dose in order to optimize radiation protection. The first aim of this study was to evaluate of the entrance surface dose (ESD) in pediatric patients undergoing chest x-ray at the main hospital of Dezful, Iran. The second aim was to compare our results with the established dose reference levels (DRL). Materials and Methods The studied population included 204 pediatric patients less than 15 year who were referred to chest x-ray. A calibrated dose area product meter (DAP-meter) with permanent installation on x-ray unit was used to radiation dose measurements. For each patient, the demographic data, exposure parameters and the dose read by DAP-meter were recorded and ESD was calculated using standard mathematical formula. Results The average value of ESD was 119 μGy in patients less than 15 years. This value was 51.3, 122.3, 131.5 and 171.2 μGy for the age groups less than 1 year, 1 to 5 year, 5 to 10 year and 10 to 15 year, respectively. A statistical significant difference was seen between ESD values ​​in different age groups (P<0.001), whereas no statistical difference was seen between ESD values in ​ girls and boys (P =0.993). Conclusion Pediatric patients in hospital investigated (except age group less than 1 year) are subjected to unnecessary radiation exposure, especially due to use of non-optimize x-ray protocols.
Keywords: Dose area product